Modern devlet ve aşiretler arasında Irak - Salihi, Emin (My University, 2011)
Aşiretler, Irak’ın en geleneksel ve köklü toplumsal kurumudur. Bu nedenle Irak’ı tanımak ve anlamak için Iraklı aşiretlerin kimlerden oluştuğu, ne tür bir toplumsal yapılarının olduğu ve toplumsal işlevlerinin dönemlere göre nasıl değiştiğini bilmek önemlidir. Çünkü aşiretlerden yola çıkarak Irak’ta iktidar-toplum ilişkisi hakkında çıkarsamalar yapılabilir. Modern dönemde İngiltere dâhil, Irak’ta tüm iktidarlar aşiretlerin toplumsal nüfuzundan faydalanmak istedi. Hatta 1990’lar sonrası Saddam Hüseyin yönetimi aşiretler ile oluşturduğu patrimonyal ilişkiler sonucunda ayakta kalabildi. ABD’nin 2003 Irak müdahalesi sonrası Irak’ta yeni bir devlet ve rejim oluşturuldu. Bu çalışma, yeni yapıda da iktidar-aşiret ilişkilerinin patrimonyal bir yapıda, yeni şartlara göre yeniden şekillendiği gözleminden yola çıkılarak başlandı. Katılımcı gözlemde bulunma ve ikinci kaynaklardan yararlanma yöntemiyle bu gözlem araştırıldı. Bunun sonucunda, aşiretlerin Irak’ta hala iktidarlar tarafından faydalanılmak istenen güçlü bir toplumsal kurum olduğu varsayımına ulaşıldı. Irak, Aşiretler, Patrimonyalizm, Kliyentalizm.

Tribes are the most traditional and rooted institution of Iraq. For that reason, it is important to know from whom Iraqi tribes are established, what kind of social structures they have and how social functions are changing within periods in order to know and understand Iraq. Because, the inferences about the power-society relations in Iraq, can be approached through tribes. In the modern era, all the rulers including England wanted to benefit from the social power of tribes. Even, Saddam Hussein administration kept up through the patrimonial relations with the tribes. After the US Intervention of Iraq in 2003, a new state and regime has been established. This work has started after the observation of the reshaped patrimonial relations between the new ruler and tribes according to new circumstances. This observation has been researched through the means of participant observation and secondary resources. As a result, the assumption that the tribes in Iraq, one powerful social institution, are still needed to be used by the rulers has been approached. Key Words: Iraq, Tribes, Patrimonialsm, Clientalism.
Keywords: Kliyentalizm; Modern Devlet; Ortadoğu_Irak; Patrimonyalizm